1999
DOI: 10.1046/j.1365-2427.1999.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the influence of recruitment from the sediment on the development of planktonic populations of cyanobacteria in a temperate mesotrophic lake

Abstract: 1. A number of planktonic cyanobacteria species form resting stages that survive in the sediments of lakes. The significance of this life history strategy to the ecology of new planktonic populations was investigated in Esthwaite Water, a mesotrophic lake in the English Lake District. 2. A simple trapping technique was used to quantify vertical movements of five species of buoyant gas‐vacuolate cyanobacteria from close to the sediments, along a depth transect. 3. ‘Recruitment’ from the sediments was found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 36 publications
2
65
2
1
Order By: Relevance
“…These findings indicate that during late autumn when ambient environmental factors such as temperature and light become unsuitable for growth and reproduction, Microcystis adapted its survival strategy to compensate for these conditions. These results indicate that colony disaggregation is one of most important survival strategies and is of vital ecological significance in the life cycle of Microcystis, which is similar to the results of other studies that have suggested Microcystis overwinters by settling on the surface of the sediment (Preston et al, 1980;Head et al, 1999;Brunberg and Blomqvist, 2002). Small colonies can absorb nutrients more efficiently than large colonies because they have larger specific The levels of significance of difference between two proximate measurements at each site are indicated by *, ** and *** for P < 0.05, P < 0.01 and P < 0.001, respectively.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings indicate that during late autumn when ambient environmental factors such as temperature and light become unsuitable for growth and reproduction, Microcystis adapted its survival strategy to compensate for these conditions. These results indicate that colony disaggregation is one of most important survival strategies and is of vital ecological significance in the life cycle of Microcystis, which is similar to the results of other studies that have suggested Microcystis overwinters by settling on the surface of the sediment (Preston et al, 1980;Head et al, 1999;Brunberg and Blomqvist, 2002). Small colonies can absorb nutrients more efficiently than large colonies because they have larger specific The levels of significance of difference between two proximate measurements at each site are indicated by *, ** and *** for P < 0.05, P < 0.01 and P < 0.001, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have indicated that most large colonies migrated downward in the water column and finally settled on a water-sediment interface for overwintering (Preston et al, 1980;Head et al, 1999). This phenomenon constitutes another important decline pathway of the Microcystis bloom and is termed colony settlement (Pathway II).…”
mentioning
confidence: 98%
“…Akinete recruitment in the littoral zone is generally higher than that from deep water and contributes more to facilitating the initiation of the blooms; several factors could explain this phenomenon (Head et al, 1999;Faithfull and Burns, 2006;Kravchuk, 2009). First, the shallowness of the littoral zone facilitates akinete germination, as the adequate light and temperature requirements for germination are more readily met for shallow rather than deep sediments (Stå hl-Delbanco and Hansson, 2002).…”
Section: Seasonal Pattern and Life Cycle Of Dolichospermum Bloomsmentioning
confidence: 99%
“…Thus, Head et al (1999) indicated that, in the Esthwaite Water, northern England, the major source of inocula for Dolichospermum flos-aquae blooms in summer were overwintering populations in the water column. In the Murray River, Australia, Baker (1999) found that a small proportion of filaments of D. circinalis in the winter water column coexisted with a large number of akinetes in the sediment.…”
Section: Seasonal Pattern and Life Cycle Of Dolichospermum Bloomsmentioning
confidence: 99%
“…Monitoring population dynamics together with growth rates would improve our understanding of the mechanisms of bloom formation in C. raciborskii, especially in light of the general importance of growth in determining the abundance of bloom-forming species (e.g. Head et al 1999, Brunberg & Blomqvist 2003. In this study, we investigated the seasonal change in the in situ net growth rate of C. raciborskii in a shallow pond in northern Taiwan.…”
Section: Introductionmentioning
confidence: 99%